PERBEDAAN SISTEM PENDIDIKAN INDONESIA DENGAN NEGARA-NEGARA DI ASIA TENGGARA - Syarifah Risyani; Jesas Kristius Sihotang; Anjas Lasuci Prastia; Aditya Putra; Riza Fahlapi (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
Indonesia's education system faces challenges such as inadequate infrastructure, variable teacher quality and frequently changing curricula, causing confusion for teachers, students and parents. Nonetheless, the government continues to improve access and quality of education. Indonesia's education system covers primary, secondary and tertiary levels, with a focus on improving the quality of life in accordance with the 1945 Constitution. In contrast, Singapore has a superior education system with a bilingual policy and a full curriculum. Compulsory education lasts for ten years, and thirteen years are required for university entrance. Malaysia has an education system from preschool to higher education, with a fixed curriculum and prioritized teacher welfare. Brunei Darussalam focuses on human capital development through a bilingual education system and the Malay Islam Beraja Concept, with the implementation of the SPN21 system that provides opportunities for students to achieve higher education. While each country has unique advantages and challenges in their education systems, all are working to improve the quality of education and human resource development for a better future.